Kvalitetsbedömning av selekterad och oselekterad hingstsperma med hjälp av flödescytometri och fluorometri, före och efter seminsäsongen - Bäckgren, Lotten (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2008)
Most Swedish Warmbloods are bred by artificial insemination (AI). Quality control of the semen consists of the subjective evaluation of motility. There is a need for a more accurate and objective method of rating the semen. In this study we compared fluorometry with flowcytometry as a method for evaluating sperm viability. Semen was collected from three stallions, stationed at Markebäcks Gård, Askersund, three times during week 15 and week 34, 2008. The semen was analyzed at 4 hour and 24 hour. This study is a part of a larger project at SLU to evaluate alternative methods for semen quality analysis and ways to improve viability and time of survival for semen by selection, so called Single Layer Centrifugation. The purpose of this study was: